Hungarian Monitoring, 27 May 1990 . [Magyar rádiófigyelő], 1990. május 27 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Russian democratic party established - Railways strike and local elections in Poland - Buying-up panic in Moscow Domestic Affairs: - IMF delegation in Budapest - Ferenc Rabár in talks in Austria about regional economic development - Gyula Horn is the president of the Hungarian Socialist Party - The national board of the Peasant Association - Wreath-laying ceremony on the occasion of the first anniversary of János Kádár death Külpolitika: - Megalakult az Oroszországi Demokrata Párt - Vasutassztrájk Lengyelországban és a helyhatósági választások - Felvásárlási láz Oroszországban Belpolitika: - IMF küldöttség érkezik Budapestre - Rabár Ferenc Ausztriában tárgyal a térség gazdasági támogatásáról - Horn Gyula az MSZP elnöke - A Parasztszövetség országos választmányi ülése - Koszorúzás Kádár János halálának egyéves évfordulóján